Gd (III) complex conjugate of low-molecular-weight chitosan as a contrast agent for magnetic resonance/fluorescence dual-modal imaging. (5th June 2016) - Huang, Yan; Boamah, Peter Osei; Gong, Jianbo; Zhang, Qi; Hua, Mingqing; Ye, Yuzhen
Highlights: Gd-DTPA-FITC-CS11 has higher binding affinity to BSA. Gd-DTPA-FITC-CS11 exhibited higher in vitro properties than commercial Gd-DTPA. Gd-DTPA-FITC-CS11 was a promising dual-modal imaging contrast agent. Abstract: The fusion of molecular and anatomical modalities facilitates more reliable and accurate detection in clinic. In this work, we prepared gadolinium (III) complex Gd-DTPA-FITC-CS11 with magnetic resonance (MR) and fluorescence dual-modal imaging modalities. Gd-DTPA-FITC-CS11 consisted of fluorescein isothiocyanate and low-molecular-weight chitosan (CS11 ) units conjugated with gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA). Gd-DTPA-FITC-CS11 exhibited a higher longitudinal relaxivity (14.09 mM −1  s −1 ) than the clinical Gd-DTPA (3.85 mM −1  s −1 ). T 1 -weighted MR contrast enhancement was also demonstrated the comparability to Gd-DTPA at lower dosage. The binding with bovine serum albumin (BSA) was investigated. The fluorescence of BSA in the presence of Gd-DTPA-FITC-CS11 was weakened due to static quenching mechanism. The conformation of BSA was slightly changed but α -helix was dominant. The binding was entropy-driven and spontaneous and the main contribution was hydrophobic interaction. Our results suggested the potential of Gd-DTPA-FITC-CS11 as an MR/fluorescence dual-modal imaging contrast agent in improving the diagnostic sensitivity and accuracy.